Problematika Penerapan Bea Perolehan Hak Atas Tanah dan Bangunan (BPHTB) terhadap Harga Jual Tanah (Deposisi: Jurnal Publikasi Ilmu Hukum, 2025)
The problem that arises is the use of transaction value as the basis for BPHTB calculations. The provisions governing the basis for BPHTB calculations are the transaction value. The use of transaction value as the basis for BPHTB calculations often causes problems in the field, because it is not uncommon for the transaction value submitted by taxpayers to be considered inappropriate by tax officials, so that when validation is carried out, it is not uncommon for officers to request that the transaction value be changed and adjusted according to the assessment. tax. This research is of a Notmative Juridical nature with the research object being the BPHTB for land sale and purchase transactions. That the legal certainty regarding the provisions for BPHTB calculations for land sale and purchase transactions regarding discrepancies between the NJOP in the Land Sale and Purchase Deed and the actual land price is that the BPHTB calculation is calculated from the NJOP PBB value stated in the SPPT PBB. The government, to provide guarantees of legal certainty regarding BPHTB, then issued a Circular Letter to the National Land Agency of the Republic of Indonesia number: 05 /SE/IV/2003 concerning Registration of Land Rights or Registration of Land Rights related to the implementation of Law Number 28 of 2009 concerning Regional Taxes and Regional Levy, which is addressed to heads of land offices throughout Indonesia. In order for there to be certainty in the payment of BPHTB, it is necessary to determine the exact value as the basis for calculating BPHTB by the authorized agency, for example by using the Value Selling Land and Building Tax Tax Objects (NJOP PBB) as outlined in the Land and Building Tax Debt Notification Letter. Building (SPPT PBB), or its value determined by the authorized agency.